Divided frontier: the George Rogers Clark expedition and multi-cultural interaction - Titus, Kenneth B. (Kansas State University, 2009)
The land west of the Alleghany Mountains and along the Ohio River and Great Lakes was an area of hotly contested land and sovereignty claims during the colonial period, complete with shifting loyalties and highly factionalized alliances. Warfare and diplomacy in the western territories often hinged on the actions of just one man or a small group of people, with consequences that could cause the collapse of entire empires. The long-standing battle for land and power throughout the Ohio Valley has been called the Long War because once conflict began between the French, British, and Indians in 1754, no one power was truly able to claim the land and its people until the British were forced out of their Great Lakes forts in 1815. George Rogers Clark uniquely united these groups for a short moment in history. A feat made all the more impressive when we consider how long the region remained contested ground between empires. These factions united only once prior the era of American control. During the expedition of George Rogers Clark in 1778, backcountry settlers, French habitants, Indian chiefs, and Spanish officials all united during a small window of time to overthrow British control of the Illinois Country. He moved freely from the top political circles of Virginia to the remote frontier outposts of the Illinois Country. This thesis argues that George Rogers Clark was especially successful at gaining the cooperation of diverse groups of populations and coordinating those groups to work together towards his own goals. Clark certainly owes part of his success to being the right man in the right place at the right time, but it must be remembered that he was the only man to ever bring all of these factionalized groups together.
Keywords: George Rogers Clark; Illinois Country; Culture in the Ohio Valley; American Revolution; French Illinois; Frontier Warfare; History, United States (0337)